THE INFLUENCE OF GRATITUDE AND SELF-ESTEEM ON PSYCHOLOGICAL HELP-SEEKING BEHAVIOR IN VOCATIONAL SCHOOL STUDENTS - Jati Setiya Ningrum; Mulawarman, Mulawarman (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2024)
The behavior of seeking psychological help shows a sign of mental health in adolescents. Seeking psychological help is influenced by various things, including gratitude and self-esteem. With gratitude, students appreciate the benefits of social support for their problems, and with self-esteem, they will raise defenses to solve their problems. This study examines the effect of gratitude and self-esteem on psychological help-seeking behavior in vocational high school students in Boja District, Kendal Regency. The population of this study was 2,504 students, and with the cluster sampling method and the calculation of the Isaac and Michael formula, 333 students were selected as the research sample. The method used in this study is a quantitative approach of correlational design with multiple regression analysis. The study results obtained an f-test score of 74.383 with a sig of 000, meaning H1 is accepted. Gratitude and self-esteem simultaneously affect 31.1% of psychological help-seeking behavior and have a significant and positive relationship. So, it can be interpreted that the higher the level of gratitude and self-esteem in students, the higher the level of help-seeking behavior.